Clinical Pharmacy Practice Patterns Among North Carolina Rural Hospitals. (April 2021) - Lanier, Cameron; Moss, Jason; Tunney, Robert; Baird, Ruthanne; Kelly, Kim
Introduction: Rural hospitals are isolated without adequate funding needed to provide for clinical services offered at larger health systems. The purpose of this study is to determine the clinical pharmacy services available and desired by rural hospitals in North Carolina. Methods: This prospective, cross-sectional, survey was distributed to a cohort of rural pharmacy directors and managers at rural hospitals across North Carolina. Data collected pertained to characteristics of the hospital and pharmacy, pharmacy director, clinical services, and responder impressions on their ability to maintain or enhance clinical services. Responses were summarized utilizing descriptive statistics and free-responses were coded for similar themes. Results: Seventeen respondents (32.6%) completed the survey. Clinical activities varied, as did characteristics of the hospitals and staff. Improved patient care is the primary reason why hospital pharmacies expand their clinical participation (46.7%). Pharmacy directors believed growth of clinical activities was a long-term goal while reporting regulations, staff, and finances as barriers to growth. Conclusion: Clinical pharmacy services vary in NC rural hospitals. Directors exhibit a willingness to expand clinical responsibilities. Rural hospital pharmacy directors desire pharmacists to be active clinically in patient care, but face barriers in reaching that goal.